Metabolic rate allometry in intertidal mussels across environmental gradients: The role of coastal carbonate system parameters in mediating the effects of latitude and temperature. (November 2022) - Labra, Fabio A.; San Martín, Valeska A.; Jahnsen-Guzmán, Nicole; Fernández, Carolina; Zapata, Javier; García-Huidobroro, M. Roberto; Duarte, Cristián; García-Herrera, Claudio; Vivanco, Juan F.; Lardies, Marco A.; Lagos, Nelson A.
Abstract: We assess the role of direct and indirect effects of coastal environmental drivers (including the parameters of the carbonate system) on energy expenditure (MR) and body mass (M) of the intertidal mussel, Perumytilus purpuratus, across 10 populations distributed over 2800 km along the Southern Eastern Pacific (SEP) coast. We find biogeographic and local variation in carbonate system variables mediates the effects of latitude and temperature on metabolic rate allometry along the SEP coast. Also, the fitted Piecewise Structural Equation models (PSEM) have greater predictive ability (conditional R 2  = 0.95) relative to the allometric scaling model ( R 2  = 0.35). The largest standardized coefficients for MR and M were determined by the influence of temperature and latitude, followed by p CO2, pH, total alkalinity, and salinity. Thus, physiological diversity of P. purpuratus along the SEP coast emerges as the result of direct and indirect effects of biogeographic and local environmental variables. Graphical abstract: Unlabelled Image Highlights: Latitude and temperature do not explain intertidal mussel metabolic rate allometry. Carbonate system parameters also have effects on size and metabolic rate. Observed allometric variation is best explained by a structural equation model. Metabolic rate allometry is modulated by multiple environmental stressors.